Captive culture of two sea snake species Hydrophis curtus and Hydrophis cyanocinctus - Kien, Nguyen Trung; An, Hua Thai; Sang, Huynh Minh; Hoang, Do Huu; Nguyen, Cao Van; Hoa, Ho Thi (Vietnam Journal of Marine Science and Technology, 2021)
Acclimation culture and trial culture of two sea snake species Hydrophis curtus and H. cyanocinctus in composite tanks were conducted to determine growth, survival rate, predation behavior and prey selection. The results showed that adults of H. curtus and H. cyanocinctus did not capture any prey such as anchovy, eel and shrimp in a period of 30 days of acclimation culture. The body weight of two these species reduced gradually from 783.3 ± 76.4 g and 360.0 ± 60.0 g to 660.0 ± 135.2 g and 315.0 ± 77.8 g, respectively. Survival rate was 100% in H. curtus and 80% in H. cyanocinctus. Meanwhile, the results of acclimation culture of sea snake juvenile revealed that frozen anchovy was preferred prey in both of two species. The body weight of H. curtus increased from 49.8 ± 0.5 g to 70.0 ± 8.2 g and that of H. cyanocinctus was 44.3 ± 3.1 g to 47.1 ± 5.2 g. The prey capture rate of H. curtus and H. cyanocinctus was 100% and 60%, respectively. Survival rate of the juvenile of two species was 100% after 30 days of acclimation culture. In 60 days of trial culture, similar results as acclimation culture were observed in adults of two sea snake species, they still did not capture any prey and the body weight reduced gradually. The result of 60-day culture of sea snake juvenile showed that the prey capture rate was 100% in both of two species. The body weight of H. curtus and H. cyanocinctus increased from 70.0 ± 8.2 g and 57.5 ± 5.8 g to 78.3 ± 15.3 g and 65.0 ± 14.1, respectively. SGR of H. curtus was 0.16 ± 0.32 %/day and that of H. cyanocinctus was 0.52 ± 0.36%/day. The survival rate of H. curtus and H. cyanocinctus was 60% and 40% in period of 60 day trial.